Online testing - The construction of a functional model in assessing student’s performance using the pedagogy of bloom’s taxonomy / Mohd Faisal Ibrahim …[et al.] - Ibrahim, Mohd Faisal; Jasmis, Jamaluddin; Elias, Shamsul Jamel; Harun, Afdallyna Fathiyah Harun (2004)
Assessment is an integral learning process that has a significant impact on what students learn and how effectively they learn. It involves the participation of both students and lecturers and can be used as a tool to gauge students’ performance. However, educational researchers are concerned if there are special education needs that are needed in measuring students’ performance. This is because, if a lecturer wants to perform efficient student evaluation, an assessment system that enfolds a tracking ability that tracks and records student’s performance on test questions and answers should be made available. Therefore, in this study, a functional model that utilizes the tracking and analysis abilities of an on-line test is constructed. The functional model constructed has successfully shown that evaluating students’ performance in terms of cognitive level knowledge, comprehension, analysis and application is possible through the implementation of the pedagogy of Bloom’s Taxonomy.